SOCIAL CLASS CONFLICT REFLECTED IN “FAR FROM THE MADDING CROWD” NOVEL BY THOMAS HARDY - Manuela Indriati Siahaan; Tomi Arianto (Universitas Putera Batam, 2020)
This research aimed to analyze social class conflict reflected in novel of Far from the Madding Crowd by Tomas Hardy. This descriptive qualitative research focuses on the social class conflict in England which is reflected in this novel. This study uses a sociological approach and analyzes the distribution of social classes in this novel and the social class conflicts that occur in this novel. The method used in writing this thesis is a qualitative descriptive method, namely the author describes, memorizes, and analyzes existing data. Quotations from books in libraries and the internet related to this research. The theory used is the theory of sociology with experts Max Weber and Karl Max.. The theory proposed by Karl Marx is an explicit theory, based on Marx's description of the laws of historical development, capitalism and socialism. Theory of sociology is used to analyze the social class divisions that exist in this novel while Maxisme class theory analyzes the conflicts. The results are have featured three male characters who became the main characters are Mr. Boldwood, Mr. Troy and Mr. Oak coming from three different classes of lower classes, middle classes, and upper classes. The social that happen among of three male character are: First, Bribery are shown conflict between Mr. Boldwood and Mr. Troy are representation to Upper Class and Middle Class. Second, Arrogance are shown conflict between Mr. Boldwood and Mr. Troy are representation to Middle Class and Upper Class. Third, are shown conflict between Mr. Troy and Mr. Oak are representation to Middle Class and Lower Class.